„Trwać w dialogu z wątpliwościami i nieznanym...”. Nowy wymiar teatru tańca na przykładzie twórczości Crystal Pite i Kidd Pivot - Banach, Anna (Relacyjność w kulturze i sztuce: Księga jubileuszowa Profesor Małgorzaty Leyko, 2025)
This article is an attempt to examine the phenomenon of Crystal Pite as an artist who, in close collaboration with Jonathon Young, creates performances for the Vancouver-based company Kidd Pivot, which contemporary critics have de-scribed as a hybrid that stretches the boundaries of theatre and dance, placing her among the most important representatives of contemporary dance theatre. Reconstructing Pite's artistic biography and emphasising its most important stages, as well as following the findings of the dancer and choreographer Robert Desrosiers and the literary critic and dance researcher Peter Dickinson, the au-thor analyses two of the three most recent artistic productions created by the Pite-Young duo for Kidd Pivot, which exemplify their shared fascination with narrative dance theatre and language as a system of signs, which in the creative process is ‘rewritten’ into a bodily dimension and choreography. All this, com-bined with the emotional layer of the Vancouver company's performances, cre-ates an innovative and unusual quality.